Debating Cultural Hybridity : Multi-Cultural Identities and the Politics of Anti-Racism - Werbner, Pnina; Modood, Tariq (Critique, influence, change., 2015)
Cultural hybridity has become one of the key buzz words of late twentieth century critical theory, cited and celebrated as a space of resistance and protest, on the one hand, and tolerance, cosmopolitanism and multiculturalism, on the other. But what are the limits of cultural hybridity? Why is it such a difficult - at times almost impossible - challenge to negotiate differences across cultures? In what ways does racism strike at the foundations of multiculturalism to create pathological cultural hybrids and ambivalences? This pathbreaking new book deconstructs established approaches and discloses why anti-racism and multiculturalism are hard roads to travel. It contains chapters by leading European sociologists and anthropologists.